Structural basis for mitoguardin-2 mediated lipid transport at ER-mitochondrial membrane contact sites - Hyunwoo Kim; Seowhang Lee; Youngsoo Jun; Changwook Lee (Nature Communications, 2022)
The ER-mitochondria contact sites are crucial for exchanging phospholipids. Here, Kim et al. present crystal structures of mitoguardin-2 (MIGA2) which reveal that MIGA2 directly binds phospholipids and transfers them between the ER and mitochondria.